Scrotal measurements and visual scores of boar testicle size correlated with testicle weight - Duane L Davis; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1977)
Scrotal measurements and visual scores of testicle size were determined for 59 boars used in nutrition and physiology studies. The best predictors of testicular weight were visual scores (average of 3 observers) and partial-circumference measurements. Though visual score was an accurate predictor within groups scored at the same time, it was not a dependable predictor when it included combined scores of groups scored at different times.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Scrotal measurements; Visual scores; Boars; Testicle weight